Spatial distributions of 13CO and CS in a carbon-rich AGB star IRC+10216 - Tuo, Juan; Yang, Xiaofeng; Sun, Jixian (Frontiers in Astronomy and Space Sciences, 2024)
IRC+10216 is the typical carbon-rich asymptotic giant branch star, and more than 100 species have been observed in its circumstellar envelope so far. The use of interferometric arrays to map molecular emission in this source has been widely reported, but to study the angular extent of molecular emission, single-dish mapping must be employed. We report here the mapping of the 13CO J = 1–0 and CS J = 2–1 lines towards IRC+10216 using the 13.7 m mm-wave radio telescope at Purple Mountain Observatory. As far as we know, these maps are the largest published 13CO J = 2–1 and CS J = 2–1 images to date. Both molecules have roughly spherically symmetric distribution, with 13CO having an emission radius of over 80″and CS extending up to ∼50″. Assuming that the two molecules are in local thermodynamic equilibrium, the column density and fractional abundance relative to H2 for 13CO and the lower limits for CS are obtained. They are 4.35 × 1016 cm−2 and > 4.72 × 1014 cm−2, and 5.25 × 10−5 and > 2.56 × 10−7 for 13CO and CS, respectively.